The teaching of surgery in the undergraduate curriculum. Part II--Importance and recommendations for change. - Agha, R; Papanikitas, A; Baum, M; Benjamin, I (2005)
In the past decade, the teaching of surgery in the undergraduate curriculum has undergone considerable changes in quantity, mode and method of delivery. This is a result of the radical reforms of higher education, the health service and the undergraduate medical curriculum. The changes are complex and require us to ask the questions: how important is the teaching of surgery in the modern medical undergraduate curriculum and is there a need for change? We aim to tackle these questions and propose practical action which medical schools can take to ensure that they deliver effective surgical teaching within the modern medical curriculum and health service.